The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1152/ajpendo.00316.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increased malonyl-CoA and diacylglycerol content and reduced AMPK activity accompany insulin resistance induced by glucose infusion in muscle and liver of rats

Abstract: Glucose infusion in rats for 1-4 days results in insulin resistance and increased triglyceride, whole tissue long-chain fatty acyl-CoA (LCA-CoA), and malonyl-CoA content in red skeletal muscle. Despite this, the relation between these alterations and the onset of insulin resistance has not been defined. We aimed to 1) identify whether the changes in these lipids and of diacylglycerol (DAG) precede or accompany the onset of insulin resistance in glucose-infused rats, 2) determine whether the insulin resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
93
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 52 publications
9
93
0
Order By: Relevance
“…Furthermore, it was demonstrated recently that altered expression or activity of AMPK might play a key role in the onset of both high-fat and high-glucose induced insulin resistance (Kraegen et al, 2006;Liu et al, 2006). In the present study, we demonstrated AMPK might also participate in aging-related fat oxidation insufficiency and insulin resistance.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, it was demonstrated recently that altered expression or activity of AMPK might play a key role in the onset of both high-fat and high-glucose induced insulin resistance (Kraegen et al, 2006;Liu et al, 2006). In the present study, we demonstrated AMPK might also participate in aging-related fat oxidation insufficiency and insulin resistance.…”
Section: Discussionsupporting
confidence: 70%
“…Recently, Kraegen EW and colleagues reported that four days of glucose infusion induced a significant decrement of AMPK activities in rats' muscles and liver, accompanied with impaired insulin signaling and glucose disposal, indicating a possible role of AMPK in glucotoxicity (Kraegen et al, 2006). Our previous study also demonstrated that impaired expression and activity of AMPK, and accordingly insufficient intracellular fatty acid oxidation, might also participate in high-fat associated insulin resistance (lipotoxicity) (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 71%
“…Recently, it has been shown that increased FA availability stimulates AMPK activity in skeletal muscle both in vitro and in vivo (10,(24)(25)(26)(27). Likewise, a diminished AMPK phosphorylation in the liver was also supported by previous works showing that TG accumulation in the liver is in association with decreased AMPK activation (27,28). Similarly, our results show that lipid oversupply produced differing effects on AMPK activation in different tissues.…”
Section: Discussionsupporting
confidence: 88%
“…Quadriceps muscle is mainly constituted by type 2a and 2b fibers, which are mainly glycolytic and have a low capacity for using fatty acids as fuel, a fact that might explain the accumulation of triglycerides in this tissue in 24-month-old rats, which are characterized by increased serum triglyceride concentration (Escrivá et al 1997). As reported by others (Kiens 2006, Kraegen et al 2006, muscle insulin resistance is rather associated with cellular levels of malonyl-CoA, fatty acyl CoA, diacylglycerol, or ceramide, than with triglyceride accumulation. Thus, more experimental work is needed to clarify the differences in mechanism underlying the differences in insulin sensitivity between oxidative and glycolytic muscles with ageing.…”
Section: Discussionmentioning
confidence: 86%